COVID-19 and Plasmodium vivax malaria co-infection - Sundus Sardar (14571097) (2020)
The ongoing outbreak of COVID-19 poses an unprecedented global health challenge. With its variety of clinical manifestations including, but not limited to, fever, cough, diarrhea, vomiting, headache, myalgia and fatigue, it may be challenging to distinguish COVID-19 from a spectrum of diseases with similar presentations, such as malaria, especially in endemic areas. Risk of concomitant infections also remains a concern owing to overburdening of healthcare services and possible scarcity of resources. We present the first reported case of confirmed COVID and malaria co-infection. In this case, we emphasize the need for vigilance from frontline clinicians for timely diagnosis and appropriate clinical management of potential co-infections in the COVID era. Other Information Published in: IDCases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.idcr.2020.e00879